Effects of social identity, self-esteem, schooling, and age on hope - Garcia Cadena, Cirilo Humberto; Daniel González, Leopoldo; Valle de la O, Adrián; Díaz, Héctor Luis; Castro, Laura K.; Téllez, Arnoldo (Universidad Nacional de Educación a Distancia, Facultad de Psicología, 2020)
Social identity theory implies knowledge, affect, and the value given to the individual as a consequence of his/her membership in a given social group. The primary objective of this study was to analyze the direct explanatory power of social identity, schooling, and age on self-esteem, as well as the indirect effects of those variables (through the mediating variable self-esteem) on hope. A non-probabilistic sample composed of 657 persons from southern Nuevo Leon was recruited (mean age = 39.75 years; SD = 16.96). The sample comprised 483 women (73.5 %) and 174 men (26.5 %), with a mean age of 39.54 years (SD = 15.97) and 40.35 years (SD = 19.5), respectively. After comparing the mean age, no statistically significant differences were found between men and women, t(655) = -.540, p = .589, d = .03, 95 % CI (-3.75, 2.13). The age of the participants composing the total sample ranged from 14 to 90 years. The sample’s number of years of schooling ranged from 0 to 15 (M = 6.87 years, SD = 2.91).